2022
DOI: 10.17485/ijst/v15i28.33
|View full text |Cite
|
Sign up to set email alerts
|

Double-Layered Porous Rayleigh Step Slider Bearings Lubricated with Couplestress Fluids

Abstract: Objective: To examine the performance of double-layered porous Rayleigh step slider bearings lubricated with couple stress fluid and to compare it with the performance of single layered porous Rayleigh step bearing. Methods: Based on the Stokes micro continuum theory of couple stress fluids, the modified Reynolds equation governing fluid film pressure is derived. Its analytical solution is and the closed form expressions for the fluid film pressure, frictional force and load carrying capacity are obtained. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The effects of the Hartmann number as well as couple-stress parameter improve the frictional force, load capacity, and coefficient of friction as observed by Hiremath et al [11]. The two layered porous step slider bearings, developed by Naduvinamani and Ganachari [12], have a work load of higher level and with a capacity to wear of a lower level than single layered porous bearings. Rahmani et al [13] were able to optimize the load capacity, force developed through interaction of surface, friction coefficient, and flow rate of lubricant of a Rayleigh step bearing.…”
Section: Introductionmentioning
confidence: 84%
“…The effects of the Hartmann number as well as couple-stress parameter improve the frictional force, load capacity, and coefficient of friction as observed by Hiremath et al [11]. The two layered porous step slider bearings, developed by Naduvinamani and Ganachari [12], have a work load of higher level and with a capacity to wear of a lower level than single layered porous bearings. Rahmani et al [13] were able to optimize the load capacity, force developed through interaction of surface, friction coefficient, and flow rate of lubricant of a Rayleigh step bearing.…”
Section: Introductionmentioning
confidence: 84%
“…When mechanical operation is under harsh conditions, the oil will transform into a non-Newtonian fluid due to factors such as temperature, and its viscosity will change with the applied shear force or strain rate [28]. Currently, many studies have shown that non-Newtonian fluid lubricants can effectively improve oil film bearing capacity and reduce contact friction [29][30][31]. Zhu et al [32] developed a comprehensive Reynolds equation for rough journal bearing under pseudoplastic lubricant flow.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Srinivasan's [17] investigation revealed that the double layer had the effect of augmenting load capacity and frictional drag while simultaneously decreasing the coefficient of friction. Comparing single and double layer porous step slider bearing with couple stress fluid, Naduvinamani and Ganachari [18] found the double porous layer to possess a superior load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%